Correlations Among Hospital Quality Measures: What "Hospital Compare" Data Tell Us. (November 2017) - Hu, Jianhui; Jordan, Jack; Rubinfeld, Ilan; Schreiber, Michelle; Waterman, Brian; Nerenz, David
A number of quality rating systems to rank health care providers have been developed over the years with the intention of helping consumers make informed health care purchasing decisions. Many use sets of individual quality measures to calculate a global rating. The utility of a global rating for consumer choice hinges on the relationships among included measures and the extent to which they jointly reflect an underlying dimension of quality. Publicly reported data on 4 quality domains—complication, mortality, readmission, and patient safety—from Centers for Medicare & Medicaid Services' Hospital Compare website were used to examine correlations among individual measures within each measure group (within-group correlations) and correlations between pairs of measures across different measure groups (between-group correlations). Modest within-group correlations were found in only 2 domains (mortality and readmission), and there were no meaningful between-group associations. These findings raise questions about whether consumers can reliably depend on global quality ratings to make informed decisions.